Diseño del sistema de gestión de calidad y caracterización del proceso para el área administrativa financiera en la empresa Posada Gonima Propiedades LTDA, basada en la aplicación de la norma ISO 9001: 2008 (2016)
System design quality management and process characterization for Administrative Financial Area in Posada Gonima Properties Company Ltd located at Carrera 13A No. 89-38 Office 719. - Nippon Building Center place Chico, based on the application of ISO 9001: 2008, an initial diagnosis of current conditions where the importance of implementing the Quality Management System in the area, with research methods that were key to the characterization of it was determined was made. Posada Gonima Properties Company seeks a differentiating factor in the market and therefore decided to implement the Quality Management System with a focus on optimizing customer service delivery since 2011. Although the administrative area was not included in this implementation as the real estate market has evolved decide ensure optimal service from all internal processes